The determinants of return intentions of Turkish students and professionals residing abroad: an empirical investigation - Nil Demet Güngör; Aysit Tansel (Institute for the Study of Labor (IZA), 2005)
The study estimates an empirical model of return intentions using a dataset compiled from an internet survey of Turkish professionals and Turkish students residing abroad. In the migration literature, wage differentials are often cited as an important factor explaining skilled migration. The findings of the study suggest, however, that other factors are also important in explaining the non-return of Turkish professionals. Economic instability in Turkey is found to be an important push factor, while work experience in Turkey also increases non-return. In the student sample, higher salaries offered in the host country and lifestyle preferences, including a more organized environment in the host country, increase the probability of not-returning. For both groups, the analysis also points to the importance of prior intentions and the role of the family in the decision to return to Turkey or stay overseas.
Keywords: F20; F22; 330; skilled migration; brain drain; return intentions; higher education; Turkey